2005
DOI: 10.1038/sj.cdd.4401713
|View full text |Cite
|
Sign up to set email alerts
|

PPARβ/δ selectively induces differentiation and inhibits cell proliferation

Abstract: Peroxisome proliferator-activated receptor (PPAR) b-null mice exhibit exacerbated epithelial cell proliferation and enhanced sensitivity to skin carcinogenesis, suggesting that ligand activation of PPARb will inhibit keratinocyte proliferation. By using of a highly specific ligand (GW0742) and the PPARb-null mouse model, activation of PPARb was found to selectively induce keratinocyte terminal differentiation and inhibit keratinocyte proliferation. Additionally, GW0742 was found to be anti-inflammatory due to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

27
133
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(169 citation statements)
references
References 30 publications
27
133
0
1
Order By: Relevance
“…Recent literatures suggest that PPAR-b activation induces the terminal differentiation of keratinocytes, coupled with the inhibition of cell proliferation (Schmuth et al, 2004;Kim et al, 2006;Burdick et al, 2006). These studies enable us to hypothesize that PPAR-b possibly has some role in the differentiation of colon cancer, and might affect the cell adhesion, migration and/or invasion that are associated with tumor differentiation.…”
Section: Introductionmentioning
confidence: 87%
“…Recent literatures suggest that PPAR-b activation induces the terminal differentiation of keratinocytes, coupled with the inhibition of cell proliferation (Schmuth et al, 2004;Kim et al, 2006;Burdick et al, 2006). These studies enable us to hypothesize that PPAR-b possibly has some role in the differentiation of colon cancer, and might affect the cell adhesion, migration and/or invasion that are associated with tumor differentiation.…”
Section: Introductionmentioning
confidence: 87%
“…Anti-inflammatory activity of PPARβ/δ and/or PPARβ/δ ligands has been shown in a number of different models including immune cells, colon epithelium, macrophages, cardiomyocytes, keratinocytes, myoblasts, endothelial cells, nerve tissue and hepatocytes Graham et al 2005;Hollingshead et al 2007b;Jakobsen et al 2006;Kim et al 2006;Nagasawa et al 2006;Peters et al 2000;Polak et al 2005;Rival et al 2002;Schmuth et al 2004;Welch et al 2003;Woo et al 2006). There is also strong evidence that ligand activation of PPARβ/δ promotes terminal differentiation in intestinal epithelium, breast and colon cancer cell lines, trophoblasts and primary keratinocytes (Aung et al 2006;Burdick et al 2007;Kim et al 2006;Marin et al 2006;Nadra et al 2006;Schmuth et al 2004;Tan et al 2001;Varnat et al 2006;Westergaard et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…There is also strong evidence that ligand activation of PPARβ/δ promotes terminal differentiation in intestinal epithelium, breast and colon cancer cell lines, trophoblasts and primary keratinocytes (Aung et al 2006;Burdick et al 2007;Kim et al 2006;Marin et al 2006;Nadra et al 2006;Schmuth et al 2004;Tan et al 2001;Varnat et al 2006;Westergaard et al 2001). Evidence from a large number of independent laboratories also shows that cell growth is inhibited by PPARβ/δ and its ligands in colonocytes, keratincytes, cardiomyocytes, fibroblasts, endothelial cells and a variety of cancer cell lines (Ali et al 2005;Aung et al 2006;Burdick et al 2007;Fukumoto et al 2005;Hollingshead et al 2007a;Kim et al 2004;Kim et al 2006;Kim et al 2005;Man et al 2007;Marin et al 2006;Martinasso et al 2006;Matthiessen et al 2005;Michalik et al 2001;Müller-Brüsselbach et al 2007;Nadra et al 2006;Ou et al 2007;Peters et al 2000;Planavila et al 2005;Schmuth et al 2004;Tan et al 2001;Teunissen et al 2007;Varnat et al 2006;Westergaard et al 2001). Given the potential of PPARβ/δ ligands as therapeutic agents, it is of great importance to determine the effect of ligand activation of PPARβ/δ on cell growth in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During mouse embryonic development, PPAR␣, -␤, and -␥ are first expressed at E13.5. Several in vitro and in vivo studies indicated that PPAR activators accelerate differentiation and cornification in fetal and adult epidermis (Hanley et al, 1998(Hanley et al, , 1999Kim et al, 2005;Komuves et al, 2000a). In addition, in PPAR␣Ϫ/Ϫ mice, cornification is delayed (Schmuth et al, 2002).…”
Section: A Notch Above the Restmentioning
confidence: 99%